Brand Extension Strategies and Their Effect on Brand Equity: A Cross-Industry Analysis - Dewi Indriani Jusuf; Erna Pujihartanti; Sheila Kurnia Putri (Universitas Negeri Makassar, 2023)
Brand extension is a popular strategy used by companies to leverage their brand equity and introduce new products or services. However, not all brand extensions are successful in enhancing brand equity. The current research investigates the brand extension strategies used by companies in Indonesia and their effect on brand equity. The objective of this research is to explore the different brand extension strategies employed by companies across various industries in Indonesia and to understand their impact on brand equity. The study aims to identify the key success factors for brand extensions and the challenges faced by companies in implementing them. This qualitative research is based on semi-structured interviews with marketing managers from different industries in Indonesia. A total of 20 marketing managers were interviewed to gather their perspectives on brand extension strategies and their impact on brand equity. The data collected from the interviews were analyzed using thematic analysis to identify common themes and patterns. The findings of this study suggest that companies in Indonesia use different types of brand extension strategies, including line extension, category extension, and brand stretching. The study also found that successful brand extensions are those that leverage the existing brand equity, have a clear fit with the brand identity, and meet the needs of the target market. On the other hand, unsuccessful brand extensions are those that have a weak fit with the brand identity, lack consumer acceptance, or dilute the existing brand equity..